Pediatric hospitalizations for respiratory infections: Before and after SARS-CoV-2 - Monteiro,Sara (2024)
Abstract Introduction: With the emergence of the COVID-19 pandemic, several non-pharmacological measures were adopted to prevent and control the transmission of SARS-CoV-2. Objective: To compare pediatric hospitalizations for acute respiratory infections (ARIs) before and after the emergence of SARS-CoV-2. Materials and Methods: This was a retrospective, observational study of admissions for ARIs in the pediatric ward of a tertiary hospital between April 2018 and March 2021. Inclusion criteria comprised: hospitalization of pediatric patients ([0-17[ years); length of stay >24 hours; and a respiratory infection diagnosis code from ICD-10. Data were collected using electronic clinical records. The first two years were considered ‘non-COVID-19 years’ (year[Y]1 and Y2), while the period between April 2020 and March 2021 was considered the ‘COVID-19 year’ (Y3). Results: A total of 783 hospitalizations were included in the analysis. There was a significant decrease in ARIs admissions in Y3 compared to Y1 and 2 (-67% from Y2 to Y3; p<0.001), with a decrease in the proportion of bronchiolitis cases (-42% from Y2 to Y3; p<0.001) and an increase in pneumonia cases (+124% from Y2 to Y3; p<0.001). There was a significant decrease in the incidence of respiratory viruses from Y2 to Y3 (76.6% vs. 56.4%; p<0.001), mainly driven by a decrease in respiratory syncytial virus (RSV; 46.8% in Y2 vs. 2.0% in Y3; p<0.001). Conversely, there was a significant increase in the incidence of rhinovirus from Y2 to Y3 (15.3% vs. 22.8%; p<0.001), and SARS-CoV-2 was identified in 31.7% of cases in Y3. More chest computed tomography scans were performed (5.6% vs. 10.9%; p<0.001) and more systemic steroids were used (26.3% vs. 40.6%; p=0.023) from Y2 to Y3. Conclusions: Population-based non-pharmacological measures implemented during the COVID-19 pandemic were associated with a reduction in pediatric hospitalizations for ARIs. The decrease in ARIs due to RSV is particularly noteworthy in this pandemic context.